BRR2a Affects Flowering Time via FLC Splicing. - Walid Mahrez; Juhyun Shin; Rafael Muñoz-Viana; Duarte D Figueiredo; Minerva S Trejo-Arellano; Vivien Exner; Alexey Siretskiy; Wilhelm Gruissem; Claudia Köhler; Lars Hennig (PLoS Genetics, 2016)
Several pathways control time to flowering in Arabidopsis thaliana through transcriptional and posttranscriptional gene regulation. In recent years, mRNA processing has gained interest as a critical regulator of flowering time control in plants. However, the molecular mechanisms linking RNA splicing to flowering time are not well understood. In a screen for Arabidopsis early flowering mutants we identified an allele of BRR2a. BRR2 proteins are components of the spliceosome and highly conserved in eukaryotes. Arabidopsis BRR2a is ubiquitously expressed in all analyzed tissues and involved in the processing of flowering time gene transcripts, most notably FLC. A missense mutation of threonine 895 in BRR2a caused defects in FLC splicing and greatly reduced FLC transcript levels. Reduced FLC expression increased transcription of FT and SOC1 leading to early flowering in both short and long days. Genome-wide experiments established that only a small set of introns was not correctly spliced in the brr2a mutant. Compared to control introns, retained introns were often shorter and GC-poor, had low H3K4me1 and CG methylation levels, and were often derived from genes with a high-H3K27me3-low-H3K36me3 signature. We propose that BRR2a is specifically needed for efficient splicing of a subset of introns characterized by a combination of factors including intron size, sequence and chromatin, and that FLC is most sensitive to splicing defects.